Selective precipitation of ammonium hexachloropalladate from leaching solutions of cemented palladium with zinc : Recovery of palladium by selective precipitation - Nguyen, Viet Nhan Hoa; Song, Si Jeong; Lee, Manseung (Journal of Mining and Metallurgy, Section B: Metallurgy, 2022)
Palladium (Pd) present in spent electroplating solutions is concentrated by cementation with zinc (Zn) metal powder. Therefore, it is necessary to recover Pd from the cemented Pd. In this work, recovery of pure Pd(IV) compounds from the leaching solutions of the cemented Pd was investigated by using selective precipitation method. It was found that the existence of Pd(IV) in the aqueous solutions is critical for the precipitation with NH4Cl. Precipitation experiments of Pd(IV) from the synthetic aqua regia solution containing Pd(IV) and Zn(II) was tested. Afterwards, the optimum conditions were applied to the recovery of Pd(IV) precipitates from the real H2SO4 and HCl leaching solutions in the presence of NaClO as an oxidizing agent. The selective precipitation resulted in the recovery of extra pure Pd(IV) compound as (NH4)2PdCl6 from real leachates under conditions of 1:30 molar ratio of Pd(IV) to NH4Cl at 60oC within 30 min. The precipitation percentage of Pd(IV) from the aqueous solutions of H2SO4 and HCl was over 99.9 and 98.2%, respectively. Compared to leaching followed by solvent extraction in terms of economics and recovery efficiency, a simple hydrometallurgical process consisting of cementation, leaching and selective precipitation was proposed for the recovery of pure Pd(IV) compounds from spent electroplating solution.